Antibody engineering of Fc effector functions - Clark, Mike (Henry Stewart Talks, 2007)
IgG structure and modes of action, Human IgG Fc receptors, Structural interactions, Engineering strategy, Selection of subclasses and effector functions, Manipulation of functions, Case study: FMAIT, Design and engineering of inhibitory Fc mutants, Functional properties, Complement mediated lysis, FcR binding, Monocyte activation, ADCC, Clinical volunteer study, Activatory mutations, Enhanced binding to FcR, Increased ADCC, Possible applications